Impact of Visual Impairments on the Education of Learners among Pastoralist Communities in Marsabit County, Kenya - Muriungi, Pamela Karambu; Mungai, Sarah Njeri (Kenya Studies Review, 2013)
Learners from pastoralist communities face peculiar challenges in accessing and continuing with education. These challenges are occasioned by the fact that the pastoral communities attach a lot of importance to pastoral production, the low population density and the challenge of ensuring that the national education policy is relevant to the lives of the pastoralist communities. The situation is worse for learners with visual impairments .Blindness impacts negatively to both the visually impaired person and to others particularly, family members. It brings problems of psychological, personal and social nature. It is on this premises that this study was designated to investigate the impact of visual impairments among learners in pastoralist communities in Logo logo school for the visually impaired in Marsabit county. The study adopted a descriptive survey design. Data was collected using questionnaires, interview guides and observation checklists. Twenty (20) learners with visual impairments, ten (10) teachers and one (I) head teacher participated in the study making a total of 31 respondents. . The analysis indicated that majority of the cases of visual impairments were caused by trachoma and lack of access to eye specialists. The school had inadequate teaching/learning resources for visually impaired learners. Majority of the teachers were male and lacked specialized training in skills for teaching learners with visual impairments .The study recommended that there is need to allocate more resources for children with special needs in pastoralist communities and innovative efforts made to increase their access to education.
Keywords: visual impairments; pastoralists; teaching/learning resources; descriptive survey